PENERAPAN PEMBELAJARAN KOOPERATIF METODE LINGKARAN DALAM LINGKARAN LUAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 11 PADANG - Rahmi, Rahmi; Putri, Anggun Leo (Prodi Pendidikan Matematika, 2013)
TheÂ purposeÂ ofÂ thisÂ researchÂ isÂ toÂ knowÂ whetherÂ studentsâÂ understandingÂ of mathematicsÂ conceptÂ byÂ usingÂ Inside-OutsideÂ CircleÂ methodÂ isÂ betterÂ thanÂ studentsâ understandingÂ ofÂ mathematicsÂ conceptÂ byÂ using conventional Â methodÂ forÂ student Â garade VIII of SMPN 11 Padang. The kind of this research is experimentalresearch, by using students in class VIII D and VIII E as samples which registered in 2011-2012 Â academic year. The instrument of this research is written test in essay form based on Â the indicator of concept understanding. Â Based on the data analysis to test the hypothesis, it is found that P-value 0.013 Â is lower thanÂ Î±=0.05, it means that Hois rejected and H1is accepted. So, it can be Â concludedÂ thatÂ studentsâÂ understandingÂ ofÂ mathematicsÂ conceptÂ byÂ usingÂ InsideOutside Circle method is better than studentsâ understanding of mathematics concept Â by using conventional method.Key Word: Lingkaran Dalam Lingkaran Luar, Pemahaman Konsep Matematis